2011
DOI: 10.1093/cid/cir735
|View full text |Cite
|
Sign up to set email alerts
|

Current Epidemiology and Trends in Invasive Haemophilus influenzae Disease--United States, 1989-2008

Abstract: Since the introduction of Hib conjugate vaccines, the incidence of invasive disease caused by H. influenzae in the United States has decreased dramatically; however, a considerable burden of non-Hib disease is still present in the oldest and youngest age groups. There is no evidence of substantial replacement disease with non-b serotypes in young children in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
127
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 24 publications
11
127
0
Order By: Relevance
“…4 Black children in the United States are at higher risk for invasive pneumococcal disease than white children [24][25][26] and appear to have a similar to slightly higher risk than white children of invasive H influenzae disease. 27 The risks of noninvasive pneumococcal and H influenzae disease, including OM, are likely to follow the same racial patterns as invasive disease. Additionally, prospective studies have shown no…”
Section: Discussionmentioning
confidence: 99%
“…4 Black children in the United States are at higher risk for invasive pneumococcal disease than white children [24][25][26] and appear to have a similar to slightly higher risk than white children of invasive H influenzae disease. 27 The risks of noninvasive pneumococcal and H influenzae disease, including OM, are likely to follow the same racial patterns as invasive disease. Additionally, prospective studies have shown no…”
Section: Discussionmentioning
confidence: 99%
“…1,5 H influenzae type f has been reported as the most frequent non-Hib capsulated strain. [5][6][7][8][9] NTHi is also considered to be a significant cause of invasive H influenzae infection.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 H influenzae type f has been reported as the most frequent non-Hib capsulated strain. [5][6][7][8][9] NTHi is also considered to be a significant cause of invasive H influenzae infection. [5][6][7][8][9][10][11][12] Several risk factors exist for invasive H influenzae infections, including malignant neoplasms, asplenia, agammaglobulinemia, alcohol use disorder, AIDS, chronic pulmonary diseases, long-term steroid use, and undergoing chemotherapy, radiotherapy, or stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the reduction in Hib carriage among Hib conjugate vaccine recipients, concern exists as to whether invasive disease due to Hif or other non-b encapsulated strains will become more prevalent due to serotype replacement (Takala et al, 1991;Urwin et al, 1996;Ward, 1996;Tsang, 2007). In fact, several investigations in North America and Europe in the post-conjugate vaccine era have indicated an increased incidence, albeit small, of invasive infections due to non-b H. influenzae, with a predominance of nontypable and Hif strains, primarily in older age groups (Urwin et al, 1996;Ladhani et al, 2010Ladhani et al, , 2012MacNeil et al, 2011;Resman et al, 2011a;Rubach et al, 2011;Ladhani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Takala et al, 1991;Urwin et al, 1996;Ward, 1996;Tsang, 2007). In fact, several investigations in North America and Europe in the post-conjugate vaccine era have indicated an increased incidence, albeit small, of invasive infections due to non-b H. influenzae, with a predominance of nontypable and Hif strains, primarily in older age groups (Urwin et al, 1996;Ladhani et al, 2010Ladhani et al, , 2012MacNeil et al, 2011;Resman et al, 2011a; Rubach et al, 2011;Ladhani, 2012).Invasive disease associated with Hif appears to disproportionately affect individuals with underlying co-morbidities, including adults suffering from chronic obstructive pulmonary disease (COPD), ethanol abuse, chronic renal disease and human immunodeficiency virus/AIDS, and children with immunoglobulin deficiencies, severe combined immunodeficiency, human immunodeficiency virus/ AIDS, malignancy and sickle-cell disease (Nitta et al, 1995;Urwin et al, 1996;Fickweiler et al, 2004;Resman et al, 2011b;Watson et al, 2011). This is in contrast to Hib, which is considered a primary pathogen able to cause disease in otherwise healthy and immunocompetent individuals, predominantly children (Morris et al, 2008 (St Geme et al, 1993, 1996Mhlanga-Mutangadura et al, 1998), PCR analysis of variability at a lipo-oligosaccharide (LOS) biosynthetic island, and assessment of their ability to resist the bactericidal activity of adult normal human serum (NHS).…”
mentioning
confidence: 99%